Structural Integrity and Edge Stiffness Evaluation of GFRP Modular Towing Tank: Analytical and Numerical Study: Analytical and Numerical Study - AR-RABAQI, MUHAMMAD A'ZOM; Muswar Muslim; Ayom Buwono; Moch Ricky Dariansyah; Mohammad Danil Arifin; ALDYN CLINTON PARTAHI OLOAN; Sulaksana Permana (International Journal of Marine Engineering Innovation and Research, 2026)
Conventional hydrodynamic testing facilities require substantial capital investment, limiting maritime research accessibility in developing nations. This study addresses the structural integrity and global stiffness challenges in designing a modular Glass Fiber Reinforced Polymer (GFRP) composite towing tank as a cost-effective alternative. A hybrid laminate configuration combining Chopped Strand Mat 450 g/m² and Woven Roving 800 g/m² was analyzed under hydrostatic loading using Classical Laminate Theory (CLT) and Finite Element Method (FEM). Analytical predictions indicated acceptable performance with 26.09 MPa bending stress and 5.95 mm deflection under fully clamped boundary assumptions. However, full-scale FEM simulation revealed critical free-edge effects, producing 41 MPa Von Mises stress and 62 mm deflection at the tank rim exceeding the L/200 serviceability limit despite maintaining a safety factor of 3.65. This study demonstrates that while the 19 mm wall thickness satisfies strength requirements per ASME RTP-1 standards, edge stiffening through horizontal rim reinforcement is essential to control excessive deformation in open-top modular configurations.